Molecular Genetic Dissection and Neonatal/Infantile Intrahepatic Cholestasis Using Targeted Next-Generation Sequencing - Togawa, Takao; Sugiura, Tokio; Ito, Koichi; Endo, Takeshi; Aoyama, Kohei; Ohashi, Kei; Negishi, Yutaka; Kudo, Toyoichiro; Ito, Reiko; Kikuchi, Atsuo; Arai-Ichinoi, Natsuko; Kure, Shigeo; et al. (The Journal of pediatrics, 2016)
To ascertain a molecular genetic diagnosis for subjects with neonatal/infantile intrahepatic cholestasis (NIIC) by the use of next-generation sequencing (NGS) and to perform a genotype-phenotype correlation. We recruited Japanese subjects with NIIC who had no definitive molecular genetic diagnosis. We developed a diagnostic custom panel of 18 genes, and the amplicon library was sequenced via NGS. We then compared clinical data between the molecular genetically confirmed subjects with NIIC. We analyzed 109 patients with NIIC (“genetic cholestasis,” 31 subjects; “unknown with complications” such as prematurity, 46 subjects; “unknown without complications,” 32 subjects), and a molecular genetic diagnosis was made for 28 subjects (26%). The rate of positive molecular genetic diagnosis in each category was 22 of 31 (71%) for the “genetic cholestasis” group, 2 of 46 (4.3%) for the “unknown with complications” group, and 4 of 32 (12.5%) for the “unknown without complications” group. The grouping of the molecular diagnoses in the group with genetic cholestasis was as follows: 12 with Alagille syndrome, 5 with neonatal Dubin-Johnson syndrome, 5 with neonatal intrahepatic cholestasis caused by citrin deficiency, and 6 with progressive familial intrahepatic cholestasis or benign recurrent intrahepatic cholestasis with low gamma-glutamyl transpeptidase levels. Several clinical datasets, including age of onset, direct bilirubin, and aminotransferases, were significantly different between the disorders confirmed using molecular genetic diagnosis. Targeted NGS can be used for molecular genetic diagnosis in subjects with NIIC. Clinical diagnosis should be accordingly redefined in the view of molecular genetic findings.